Aplikasi Android Untuk Pengaman Teks Menggunakan Kriptografi Berlapis Dengan Algoritma Caesar, Blowfish Dan Aes (Advanced Encryption Standar) - Fernanda Fitriansyah; Ery Safrianti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Rapid technological developments in the telecommunications sector provide benefits that can facilitate communication from one place to another. Technological developments are also required to improve security. Along with that the security of the information exchanged is also very necessary to avoid things that are not desirable. One method of securing information and messages is to use data encryption and description, which is studied in the field of cryptography. To overcome the security problems mentioned above, this research makes an Android Application for Text Safeguards Using Layered Cryptography with Caesar, Blowfish and AES Algorithms (Advanced Standard Encryption). This application can be run on the Android 5.0 (lollipop) or above, which can be used to encrypt and decrypt text messages..Keywords: Security, Cryptology, Caesar, Blowfish, AES.